Multi-epitope chimeric vaccine designing and novel drug targets prioritization against multi-drug resistant Staphylococcus pseudintermedius - Jaan, Samavia; Shah, Mohibullah; Ullah, Najeeb; Amjad, Adnan; Javed, Muhammad Sameem; Nishan, Umar; Mustafa, Ghazala; Nawaz, Haq; Ahmed, Sarfraz; Ojha, Suvash Chandra (Frontiers in Microbiology, 2022)
Biofilm synthesizing multi-drug resistant Staphylococcus pseudintermedius bacteria has been recognized as the human infectious agent. It has been detected in the diseases of skin, ear, and postoperative infections. Its infections are becoming a major health problem due to its multi-drug resistance capabilities. However, no commercial vaccine for the treatment of its infections is currently available in the market. Here we employed the subtractive proteomics and reverse vaccinology approach to determine the potential novel drug and vaccine targets against S. pseudintermedius infections. After screening the core-proteome of the 39 complete genomes of S. pseudintermedius, 2 metabolic pathways dependent and 34 independent proteins were determined as novel potential drug targets. Two proteins were found and used as potential candidates for designing the chimeric vaccine constructs. Depending on the properties such as antigenicity, toxicity, and solubility, multi-epitope based vaccines constructs were designed. For immunogenicity enhancement, different specific sequences like linkers, PADRE sequences, and molecular adjuvants were added. Molecular docking and molecular dynamic simulation analyses were performed to evaluate the prioritized vaccine construct's interactions with human immune cells HLA and TLR4. Finally, the cloning and expression ability of the vaccine construct was determined in the bacterial cloning system and the human body immune response was predicted through immune simulation analysis. In conclusion, this study proposed the potential drug and vaccine targets and also designed a chimera vaccine to be tested and validated against infectious S. pseudintermedius species.